Sound production by the Lusitanian toadfish, Halobatrachus didactylus - Santos, Manuel Eduardo dos (2012)
Several batrachoidids have been known to produce sounds associated with courtship and agonistic interactions, and their repertoires have been studied acoustically and behaviourally. In contrast, sound production of the Lusitanian toadish Halobatrachus didactylus, although often noted, has not been acoustically studied. This sedentary predator of Northeastern Atlantic coastal waters is usually found in sandy and muddy substrates, under rocks or crevices. Sound recordings were made in Ria Formosa, a lagoon complex in southern Portugal. The sound producing apparatus was studied in adult individuals of both sexes captured by local fishermen. It is shown that this species produces acoustic emissions similar to other batrachoidids. It produces a long, rhythmical, tonal sound, often in choruses, which is comparable to the boatwhistle or hum signals of Opsanus and Porichthys, and a complex of signals that were classified as grunts, croaks, double croaks and mixed calls ('grunt-croak’). As in other toadfishes, H. didactylus presents sonic muscles connected to a bi-lobed swimbladder. Asynchronous contractions of the sonic muscles were detected when massaging the ventral surface of the fish.